Unmanned Electric Tugboat Formation Multi-Agent Energy-Aware Control System Concept - Wojciech Koznowski; Andrzej Łebkowski (Energies, 2022)
The topic of reducing exhaust gas emissions from internal combustion engines in the areas of port and coastal waters is in line with the assumptions of the climate policy. The publication presents a proposal to reduce the energy associated with the movement of port vessels through the use of a specific pattern (shape and size) of their movement. In addition to controlling the formation of tugboats, the authors propose the use of a multi-agent system offering elements of autonomous control of the vessels, which adjusts the parameters of the formation depending on the tasks performed. The results of tests for four tugboats with a hull length of 32 m and a maximum speed of 13 knots, moving in formations of eight different configurations, were analyzed. Studies conducted on the basis of a simulated exit and return to port scenario at a distance of 11.4 nm showed the possibility of reducing energy consumption required for movement by 5.8% to even 57.6% for tugboats moving one after another, at a certain distance. In addition, in order to completely eliminate exhaust gas emissions from the engines, it is proposed to use tugboats with electric drive together with an appropriate energy storage charging infrastructure.